Development and application of algorithms for simulating terraces within SWAT - Shao, Hui; Baffaut, Claire; Gao, Jian’en; Nelson, Nathan O.; Janssen, Keith A.; Pierzynski, Gary M.; Barnes, Philip L. (My University, 2014)
Terraces have been proven to be an effective conservation practice for controlling high soil loss. In large hydrological programs such as the Soil and Water Assessment Tool (SWAT), terrace effects are simulated by adjusting the slope length and the USLE P-factor. In this study, a process-based terrace algorithm was developed and incorporated into SWAT (version 2009) to simulate the environmental effects of different kinds of terraces, i.e., normal and bench terraces. The terrace algorithm was activated at the hydrological response unit (HRU) level. Terrace description, storage effects, and the flow interaction between the terraces and the HRU were also introduced in the method. The modified SWAT model was evaluated using a four-year, six-plot event runoff and sediment data set with five years of plant yield data collected on a natural rainfall terraced field in southeast Franklin County, Kansas. Results indicated that the model’s performance was satisfactory in simulating single and average plot runoff as well as average plot sediment yields, with Nash-Sutcliffe efficiencies always greater than 0.5 and often greater than 0.7. The model’s performance was less consistent in simulating sediment yields from the no-till plots. The development and incorporation of the terrace algorithm provide a process-based alternative to the use of the P-factor in representing the effectiveness of terraces.
Keywords: Algorithm development; Erosion; Runoff; SWAT model; Terraces